Comparative Effects of Intraduodenal Glucose and Fat Infusion on Blood Pressure and Heart Rate in Type 2 Diabetes - Xie, Cong; Wang, Xuyi; Jones, Karen L.; Horowitz, Michael; Sun, Zilin; Little, Tanya J.; Rayner, Christopher K.; Wu, Tongzhi (Frontiers in Nutrition, 2020)
The interaction of nutrients with the small intestine modulates postprandial cardiovascular function. Rapid small intestinal nutrient delivery may reduce blood pressure markedly, particularly in patients with type 2 diabetes (T2DM). Postprandial hypotension occurs in ~30% of patients with longstanding T2DM, but there is little information about the cardiovascular effects of different macronutrients. We compared the blood pressure and heart rate responses to standardized intraduodenal glucose and fat infusions in T2DM. Two parallel groups, including 26 T2DM patients who received intraduodenal glucose infusion and 14 T2DM patients who received intraduodenal fat, both at 2 kcal/min over 120 min, were compared retrospectively. Blood pressure and heart rate were measured at regular intervals. Systolic blood pressure was stable initially and increased slightly thereafter in both groups, without any difference between them. Diastolic blood pressure decreased in response to intraduodenal glucose, but remained unchanged in response to lipid, with a significant difference between the two infusions (P = 0.04). Heart rate increased during both intraduodenal glucose and lipid infusions (P < 0.001 each), and the increment was greater in response to intraduodenal fat than glucose (P = 0.004). In patients with T2DM, intraduodenal fat induced a greater increase in heart rate, associated with a diminished reduction in blood pressure, when compared with isocaloric glucose. The macronutrient composition of meals may be an important consideration in T2DM patients with symptomatic postprandial hypotension.